Blood Cell Parameters Among Stable Ambulatory Hypertensive Patients and Non-Hypertensive Population - a cross sectional study - Mahaseth, Aditya; Shah, Rajesh; Singh, Amit Kumar; Lamichhane, Aayush (Journal of Advances in Internal Medicine, 2025)
BACKGROUND Hypertension is a prevalent condition associated with increased cardiovascular risk. Altered blood cell parameters have been implicated in the pathophysiology of hypertension, but their specific role remains unclear.Objective: This study aimed to compare blood cell parameters among stable ambulatory hypertensive patients and a non-hypertensive population.METHODS A cross-sectional study was conducted, recruiting 500 participants (250 hypertensive and 250 non-hypertensive individuals) from Shahid Gangalal National Heart Centre Janakpur. Demographic information, medical history, and blood pressure measurements were collected. Venous blood samples were analyzed for red blood cell (RBC) count, white blood cell (WBC) count, platelet count, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC).RESULTS Hypertensive patients exhibited a higher platelet count (298.2 ± 45.6 × 10⁹/L) compared to the non-hypertensive group (271.4 ± 39.2 × 10⁹/L) (p < 0.05). No significant differences were observed in RBC count, WBC count, MCV, MCH, or MCHC between the two groups (p > 0.05).CONCLUSION This study provides insights into the differences in blood cell parameters between stable ambulatory hypertensive patients and non-hypertensive individuals. The findings suggest a potential role of platelets in hypertension, warranting further investigation.